SHELF LIFE OF NORI FROM Gracilaria sp. WITH ALUMUNIUM FOIL PACKAGING BASED ON THE ACCELERATED SHELF LIFE TEST METHOD - Evi Liviawaty; Sapinatun Namira; subiyanto subiyanto; Eddy Afrianto (Research Collaboration Community (RCC), 2021)
This research was conducted at the Laboratory of Fisheries Products Processing, Faculty of Fisheries and Marine Sciences, Padjadjaran University, Jatinangor. The purpose of this research is to determine the shelf life of Nori from Gracilaria sp. with the Accelerated Shelf Life Test (ASLT) method Arrhenius Model using Aluminum Foil packaging. Aluminum foil packaging is a package composed of hermetic, flexible, and opaque metal so that it has high protection properties against water vapor, light, grease and gas. The determination of the shelf life of the ASLT method is carried out using parameters of environmental conditions that can accelerate the process of product quality degradation, namely by storing the product at several temperatures above normal storage temperature. The observations used in determining the shelf life of Gracilaria sp. using a sensory test and a water content test with storage for 35 days, at a temperature of 25oC and 35oC. The result of the Arrhenius model calculation, the appearance parameter is selected as the critical parameter because it has the lowest Activation Energy (Ea) in determining the shelf life of Gracilaria sp. which is packaged using PE plastic. The results show that the parameters used to determine the shelf life of the product are the taste parameters based on the order 1 reaction with the Arrhenius Plot Ln K = 0.026 – 1318.4 (1 / T) and Ea of 2619.66 Kj/mol. The shelf life of Nori Gracilaria sp. if stored at 25oC temperature is 89 hari 7 jam.